KUALITAS PELAYANAN PUBLIK (STUDI PADA PENGUJIAN KENDARAAN BERMOTOR PADA UNIT PELAKSANA TEKNIS DAERAH KOTA MATARAM) - Jumaah, Siti Hidayatul; Vidya Yanti Utami; Ibnu Aswandi (Nusantara Hasana Journal, 2025)
Excellent service quality is the desire of all people, but until now there are still many public services whose quality is not in accordance with what is expected by the community. Motor Vehicle Testing Services are services whose quality needs to be improved considering that this testing is important to ensure that vehicles operated on the road meet technical and roadworthy requirements and do not pollute the environment. This study aims to analyze the quality of public services with a focus on the study of the UPTD PKB of Mataram City. The method used is descriptive qualitative with primary and secondary data types, data collected through observation, interviews and documentation, while data analysis techniques use interactive analysis. The results of the study show that the quality of service is in the good category. The physical evidence aspect which includes the testing building, administrative service building, and other supporting facilities are in good condition and provide comfort. Reliability which includes timeliness, cost, and service procedures also shows good results, although service time needs to be improved. The responsiveness aspect is classified as good, where service officers have the skills to handle complaints. Service officers also show good empathy through attention, seriousness, and sympathy for the needs of the community. Meanwhile, the guarantee aspect can also be said to be good, because the quality of the officers has qualifications and competence even though in terms of quantity it needs to get additional personnel.